2021
DOI: 10.1007/s12325-021-01783-x
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma In Situ: A Critical Review and Re-Evaluation of Current Excision Margin Recommendations

Abstract: Most international clinical guidelines recommend 5-10 mm clinical margins for excision of melanoma in situ (MIS). While the evidence supporting this is weak, these guidelines are generally consistent. However, as a result of the high incidence of subclinical extension of MIS, especially of the lentigo maligna (LM) subtype, wider margins will often be needed to achieve complete histologic clearance. In this review, we assessed all available contemporary evidence on clearance margins for MIS. No randomized trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…2 Reported recurrence rates vary from 6% to 20% following wide local excision (WLE) using the guideline-recommended 5 mm surgical margins for melanoma in situ. 3,4 As a result, international LM guidelines acknowledge larger margins (i.e. 5-10 mm) may be necessary to achieve local control, while for LMM the larger surgical margins are defined according to the tumour thickness.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…2 Reported recurrence rates vary from 6% to 20% following wide local excision (WLE) using the guideline-recommended 5 mm surgical margins for melanoma in situ. 3,4 As a result, international LM guidelines acknowledge larger margins (i.e. 5-10 mm) may be necessary to achieve local control, while for LMM the larger surgical margins are defined according to the tumour thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the optimal surgical management and margins for LM/LMM are still a matter of debate. 3 Mohs' micrographic surgery (MMS) allows intra-operational en face assessment of the surgical margins. Unfortunately, MMS is not only limited by requiring extensive training, but more importantly, the use of frozen sections is not universally accepted in the treatment of melanocytic lesions as it can result in artefactual and fixational changes in the excisional specimens.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Friedman et al performed a review of current excision margin recommendations for melanoma in situ in 2021. 13 The authors reported that the rate for a complete excision with a 5 mm margin was variable, ranging from 42% to 70%, according to the studies. The present study observed a rate of 84%.…”
Section: Discussionmentioning
confidence: 99%